Medical Assistance in Dying: Where Is International Human Rights Law Heading? - Miró Quesada Gayoso, Josefina (2025)
In recent years, the debate around legalizing medical assistance in dying (MAID) has gained momentum worldwide. Sociocultural changes, advancements in bioethics, and statements from international organizations have contributed to an increase in the number of countries considering regulating MAID. However, the debate is still characterized by legal tensions between human rights such as the right to life, freedom, privacy, and personal integrity. This article analyzes the current state of International Human Rights Law (IHRL) in relation to the legalization of MAID. It examines the standards established by both regional and universal human rights systems, focusing on the caselaw of the European Court of Human Rights (ECtHR) and the statements issued by oversight bodies. The article aims to respond to what extent MAID is compatible with IHRL and what obligations states have when addressing this issue. Finally, it offers reflections on the criteria that should be considered when legislating this practice.